Immune Profiles in Multisystem Inflammatory Syndrome in Children with Cardiovascular Abnormalities - Nathella Pavan Kumar; Aishwarya Venkataraman; Arul Nancy; Nandhini Selvaraj; Kadar Moideen; Shaik Fayaz Ahamed; Rachel Marriam Renji; Kandasamy Sasidaran; Sandip Kumar; Muthiah Periyakuppan; Thankgavelu Sangaralingam; Poovazhagi Varadarajan; et al. (Viruses, 2023)
Background: Multisystem inflammatory syndrome in children (MIS-C), a sequela of severe acute respiratory syndrome coronavirus-2 infection (SARS-CoV2), has been progressively reported worldwide, with cardiac involvement being a frequent presentation. Although the clinical and immunological characteristics of MIS-C with and without cardiac involvement have been described, the immunological differences between cardiac and non-cardiac MIS-C are not well understood. Methods: The levels of type 1, type 2, type 17, other proinflammatory cytokines and CC chemokines and CXC chemokines were measured using the Magpix multiplex cytokine assay system in MIS-C children with MIS-C cardiac (MIS-C (C) (n = 88)) and MIS-C non-cardiac (MIS-C (NC) (n = 64)) abnormalities. Results: MIS-C children with cardiac manifestations presented with significantly increased levels of cytokines such as IFN-γ, IL-2, TNFα, IL-5, IL-1α, IL-1β, IL-6, IL-10 and IL-12p70 and chemokines such as CCL2, CCL3, CCL11 and CXCL10 in comparison to MIS-C children without cardiac manifestations. Clustering analysis revealed that cytokines and chemokines could clearly distinguish MIS-C children with and without cardiac manifestations. In addition, these responses significantly diminished and normalized 9 months after treatment. Conclusions: This is one of the first studies characterizing and differentiating systemic inflammation in MIS-C with and without cardiac involvement from a low- and middle-income country (LMIC). Our study contributes to the existing body of evidence and advances our knowledge of the immunopathogenesis of MIS-C in children.